Analysis of Student Errors in Solving Ordinary Differential Equations Based on SOLO Taxonomy. (May 2020) - Yarman, Y; Fauzan, A; Armiati, A; Lufri, L
Abstract: This study aims to describe the errors of student in solving ordinary differential equation (ODE) problems based on SOLO taxonomy. In this case there are 5 kinds of errors, namely concept errors, using data, language interpretation, technical, and making conclusions. This descriptive study involved 10 ODE research subjects. The research results obtained are the subjects of research tends to make mistakes in the five SOLO taxonomy errors. The reason is because students are not skilled in using formulas, are not thorough, and the habit of not repeating lessons.